2015
DOI: 10.3389/fphy.2015.00083
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effect on magnetism in metallic ultra-thin films

Abstract: Citation:Chiba D (2015) Electric field effect on magnetism in metallic ultra-thin films. Front. Phys. 3:83. doi: 10.3389/fphy.2015.00083 Electric field effect on magnetism in metallic ultra-thin films Daichi Chiba * Department of Applied Physics, The University of Tokyo, Tokyo, JapanRecent experimental developments on the electric field effect on magnetism in metallic magnetic materials are reviewed. The change in the electron density at the surface of metallic ultra-thin magnets by the application of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…An ionic gate, however, dramatically raises the 𝑻 𝒄 up to room temperature, significantly higher than the bulk 𝑻 𝒄 of 205 Kelvin. The gate-tunable room-temperature ferromagnetism in twodimensional Fe3GeTe2 opens up opportunities for potential voltage-controlled magnetoelectronics 14,15 based on atomically thin van der Waals crystals.…”
mentioning
confidence: 99%
“…An ionic gate, however, dramatically raises the 𝑻 𝒄 up to room temperature, significantly higher than the bulk 𝑻 𝒄 of 205 Kelvin. The gate-tunable room-temperature ferromagnetism in twodimensional Fe3GeTe2 opens up opportunities for potential voltage-controlled magnetoelectronics 14,15 based on atomically thin van der Waals crystals.…”
mentioning
confidence: 99%
“…More intriguing, electrical switching of FeCo and CoFeB ultrathin films in magnetic tunnel junctions (MTJs) has also been realized, laying the groundwork for their potential applications in MRAM [33][34][35][36][37][38]. For more details about the electric-field effects on magnetism in metals, the readers can refer to several recent review papers [19,[37][38][39]. Besides, combining the ferroelectric and ferromagnetic materials in a heterostructure, non-volatile electric-field control of magnetism in (Ga,Mn)As has also been demonstrated [40].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the gate voltage-controlled magnetic anisotropy first demonstrated in DMS [17,18,21] was utilized in ferromagnetic metal based MTJs [33][34][35][36][37][38][39]. On the other hand, it continues to be of fundamental interest to explore new means and examine the extent of tuning the magnetism reversibly with minimal changes in temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an experimental point of view, through the tip of a scanning tunneling microscope the EEF can be applied locally to the system. Previous experimental studies reported that magnetization, magnetic exchange interactions, and magnetic anisotropy can be controlled and modified by EEF in multiferroic heterostructures (due to coupling between electric field with magnetization through electric polarization), metal thin films (due to shifting of the Fermi level at the interfaces), semiconductors (due to change in charge carrier density), nanomagnets, magnetic tunnel junctions (MTJs) , (due to change in charge carrier population), and magnetic nanomesh . In addition, first-principles calculations also reported that the magnetism exhibited in the nanostructures like magnetic clusters, MTJs, metallic surfaces, metallic thin films, and so on can be controlled through EEF. ,, However, manipulation of magnetism in a TM cluster above a 2D nonmetallic planar heterostructures by simultaneous variation of EEF and concentration fraction of the substrate has rarely been reported.…”
Section: Introductionmentioning
confidence: 98%